Back Cover: Facile Formation of Thermodynamically Unstable Novel Borohydride Materials by a Wet Chemistry Route (Chem. Eur. J. 15/2015). Issue 15 (7th April 2015) - Jaroń, Tomasz; Wegner, Wojciech; Fijałkowski, Karol J.; Leszczyński, Piotr J.; Grochala, Wojciech
<x xml:space="preserve">Abstract</x> A new wet chemistry method bypasses difficulties encountered in the preparation of complex metal borohyrides free from LiCl "dead mass" and it also solves all technical problems with a "one‐shot" metathetic reaction. The new reaction scheme utilizes metal cations and complex metal–borohydride anions, which are weakly solvated in organic solvents. It even allows for facile formation of thermodynamically unstable novel borohydride materials. For more details see the Communication by W. Grochala et al. on page 5689 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>